Accelerated simulation‐driven design optimisation of compact couplers by means of two‐level space mapping. Issue 7 (1st May 2015) - Bekasiewicz, Adrian; Koziel, Slawomir; Pankiewicz, Bogdan
Abstract : In this study, the authors discuss a robust and efficient technique for rapid design of compact couplers. The approach exploits two‐level space mapping (SM) correction of an equivalent circuit model of the coupler structure under design. The first SM layer (local correction) is utilised to ensure good matching between the equivalent circuit and the electromagnetic model at the component level. Subsequent global correction allows for accounting the electromagnetic couplings between the components. The important advantage of two‐level model correction is that small number of parameter is utilised at each stage, which substantially simplifies and speeds up the parameters extraction procedure. Another advantage is that the local‐global SM results in considerably better generalisation capability of the surrogate model (as compared to conventional SM). This leads to improved reliability of the optimisation process and its reduced computational cost. The proposed technique is validated using an example of two compact microstrip rat‐race couplers and compared with other surrogate‐based optimisation techniques.